Measurement of Moment of Inertia Through a Bifilar Pendulum Swing Based on a Microcontroller - Niken Tri Widayati; Nadia Wahyu Lurinda; Hartono Hartono; Supriyadi Supriyadi (Journal of Natural Sciences and Mathematics Research, 2019)
Every object has a tendency to maintain its state of motion. The concept also applies to rotating objects called moments of inertia. This experiment aims to explain the working principle and determine the magnitude of the moment of inertia of objects using a bifilar pendulum teaching aid based on the ATMEGA-16 microcontroller. The implementation method used is the experimental method. The working principle of the ATMEGA-16 bifilar pendulum microcontroller-based teaching aids uses the bifilar pendulum principle. The moment of inertia of an object can be measured using a measuring tool that works at the moment of the inertia oscillation method. The bifilar pendulum experiment consists of an object which is tied on either side by a rope and then attached to a support. Objects are deviated horizontally with a small angle to the equilibrium position and then released, the object will experience periodic oscillations. Based on the experimental results the shorter the distance of the two bifilars, the period will be even greater, and vice versa. The magnitude of the period (T) on the bifilar pendulum is inversely proportional to the root distance between the two bifilar (d). The results of experiments carried out for variations in rope length and the distance between the ropes. The moment of inertia based on experiments for variations in length of rope at 0.35 m is (I ± ΔI) =   kg/m2 ; 0.45 m is (I ± ΔI) =   kg/m2 ; 0.55 m then (I ± ΔI) =   kg/m2 ; 0.65 m then (I ± ΔI) =   kg/m2 and 0.75 m, (I ± ΔI) =   kg/m2.. Furthermore, the moment of inertia is based on experiments for variations in the distance between the ropes at 0.1 m then (I ± ∆I) =  kg/m2; 0.15 m then (I ± ∆ I) =  kg/m2; 0.20 m then (I ± ∆I) =  kg/m2; and 0.25 m then (I ± ∆I) =  kg/m2. The experimental results show that the smaller the distance between the two ropes will produce conformity to the theory of the solid cylinder using the shaft approach through the center.©2019 JNSMR UIN Walisongo. All rights reserved.